PENDEKATAN SAINS TEKNOLOGI MASYARAKAT (STM) DALAM PEMBELAJARAN - Roni Faslah (Jurnal Ilmiah Econosains, 2013)
ABSTRACTInfluences of globalization are getting felt together with the increasing of variety kinds of information providers in the form of press released or unreleased, broadcast or not broadcast, electronic or not electronic information providers, such as, newspaper, magazine, radio television, facsimiles, computer, internet, communication satellite. Improvement of technology of communication and information inclined to influence the condition of social aspect, economic aspect, culture, and also the condition of education. The applications of communication and information are giving the possibility to create global learning condition which is connected to the link that put students in the central of learning process and surrounded by many kinds of electronic learning source. Base on all of that, conventional education should be softer by accepting new style of learning which is completed by improved technology. We really need human beings, who can get along with the improvement of technology, who have knowledge of tools, source and process where knowledge is put as the central of the soul, comprehended and used in their live to increase the quality of work in the purpose of getting better prosperity in their life. The elements of human which are improved in the aspect of technology are power of thinking, power of heart, and physical power.Keywords: globalization, learning, communication and information technology